(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this article, we investigate the concept of fermatean fuzzy characteristic subgroup of a group and fermatean fuzzy normal subgroup. The level subset of fermatean fuzzy subgroup and its properties also defined. Finally, the homomorphic image of fermatean fuzzy subgroup is also discussed.